Analisis Kepuasan Kerja Karyawan Dalam Upaya Peningkatan Kinerja Pegawai Kantor Bupati Bagian Ekonomi Dan Sumber Daya Alam Kab.Aceh Singkil - Nadia Ulfa; Sri Sudiarti (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
Human resources are important because they affect the efficiency and effectiveness of the organization. One of the things that needs to be considered in HR management is employee performance. High employee performance is of course highly expected by every company because it will encourage the development of the company. The purpose of this research is to determine and analyze employee job satisfaction in an effort to improve employee performance in the Regent's Office in the field of Economics and Natural Resources, Aceh Singkil Regency. The research method used is qualitative descriptive method. The results of the research show that there is a sense of injustice felt by honorary employees. Because they feel that the existing compensation system is not transparent enough. This is of course a separate note for the agency to be able to measure how satisfied employees are with the existing compensation system. In creating job satisfaction, the management of the Regent's Office for Economics and Natural Resources, Aceh Singkil Regency, through the HR department, has focused on creating job satisfaction through three aspects, namely good HR management, a supportive work place and atmosphere, and an organizational culture that is in accordance with the agency's needs.